2010
DOI: 10.1016/j.ijdevneu.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal effect of methamphetamine on nociception in adult Wistar rats

Abstract: Methamphetamine is a psychostimulant drug which causes the release of monoamine neurotransmitters. Although drugs of abuse are known to have analgesic effects, there is a lack of evidence regarding the effect of prenatal exposure to methamphetamine on nociception in adulthood. Adult Wistar rats whose mothers had received daily exposure to methamphetamine (5 mg/kg; s.c.) or saline, during gestation or gestation and lactation periods, were examined for: (1) gender differences in nociception; (2) an association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Our findings showing decreased analgesic effect on forelimbs and hind limbs but not the tail in prenatally MA-exposed relative to prenatally saline-exposed rats suggest long-term effect of prenatal MA exposure affecting especially supraspinal analgesic mechanisms (Zemlan et al, 1984;Roerig and Fujimoto, 1988). The anti-analgesic effect of prenatal MA exposure is supported by our previous studies (Šlamberová et al, 2011b;Yamamotová et al, 2011) as well as studies of others (Chen et al, 2010). Chen et al suggested that prenatal MA exposure could predispose an alteration in the development of nociceptive neuronal network, which leads to a long-lasting status of hypersensitivity to pain stimulations in the offspring.…”
Section: )supporting
confidence: 67%
See 1 more Smart Citation
“…Our findings showing decreased analgesic effect on forelimbs and hind limbs but not the tail in prenatally MA-exposed relative to prenatally saline-exposed rats suggest long-term effect of prenatal MA exposure affecting especially supraspinal analgesic mechanisms (Zemlan et al, 1984;Roerig and Fujimoto, 1988). The anti-analgesic effect of prenatal MA exposure is supported by our previous studies (Šlamberová et al, 2011b;Yamamotová et al, 2011) as well as studies of others (Chen et al, 2010). Chen et al suggested that prenatal MA exposure could predispose an alteration in the development of nociceptive neuronal network, which leads to a long-lasting status of hypersensitivity to pain stimulations in the offspring.…”
Section: )supporting
confidence: 67%
“…Further, we found that prenatal MA exposure with respect of adult MA challenge impairs the learning abilities tested in Morris water maze (Schutová et al, 2008), affects anxiety behavior , alters pain sensitivity in Plantar tests in sex-specific manner (Yamamotová et al, 2011) and seizure susceptibility in adult male and female rats Bernášková et al, 2011). In our most recent studies we demonstrated that there is a sensitizing effect of prenatal MA exposure to the same drug in adulthood (Bubeníková-Valešová et al, 2009;Šlamberová et al, 2011a, b).…”
Section: Introductionmentioning
confidence: 60%
“…The dopaminergic system, in terms of pain, has received much less attention, although stimulants like amphetamine or methamphetamine are highly effective analgesics (Yamamotová et al, 2011; Yamamotová and Šlamberová, 2012). Pain is modulated by D2 receptors, particularly within the mesolimbic dopaminergic system and the nucleus accumbens, hence in the “reward system” of the brain (Franklin, 1998; Altier and Stewart, 1999; Wood, 2006).…”
Section: Common Neurobiological Mechanisms Of Pain and Depressionmentioning
confidence: 99%
“…Among the different dosing regimens, throughout the entire gestation is the most commonly used duration of exposure (Bubenikova-Valesova et al, 2009;Schutova et al, 2009;Yamamotova et al, 2011). This dosing regimen relates to the clinical situation where the mother is abusing MA everyday throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%